The wedding people : a novel [large type] - Espach, Alison, 1984- (Thorndike Press large print top shelf., 2024)
"It's a beautiful day in Newport, Rhode Island, when Phoebe Stone arrives at the Cornwall Inn. She's immediately mistaken by everyone in the lobby for one of the wedding people, but she's actually the only guest who isn't here for the big event. Phoebe is here because she's dreamed of coming for years. She hoped to shuck oysters and take sunset sails with her husband, only now she's here without him, at rock bottom, and determined to have one last splurge on herself. Meanwhile, the bride has accounted for every possible disaster except for, well, Phoebe and Phoebe's plan--which makes it that much more surprising when the two women can't stop confiding in each other"--